Implementasi Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK-EMKM) dalam Penyusunan Laporan Keuangan pada Toko Sinar Berkah Kabupaten Deli Serdang - Angga Laksana; Sugianto Sugianto; Rahmat Daim Harahap (Universitas 45 Surabaya, 2024)
This research aims to analyze the suitability of financial reports based on the application of accounting based on SAK EMKM at the UKM Toko Sinar Berkah Deli Serdang Regency located on Jl. No. 1 defense 5, Hamlet 6, Laut Dendang Village, Deli Serdang Regency, North Sumatra. This research was conducted using qualitative methods with a descriptive approach and the application of recording financial reports based on SAK EMKM using primary and secondary data taken from Toko Sinar Berkah, Deli Serdang Regency. The data collection technique in this research uses interview techniques and the analysis techniques used are data reduction, data presentation and drawing conclusions. Based on data analysis, the research results show that the owner of Sinar Berkah Shop does not understand SAK-EMKM. Toko Sinar Berkah Deli Serdang Regency has implemented accounting but the recording of financial reports is still done manually and is very simple and its implementation does not follow the provisions in SAK EMKM. The financial report prepared by Toko Sinar Berkah, Deli Serdang Regency is only in the form of a profit and loss report, while the financial position report and notes to the financial report have not been implemented. The Profit and Loss Report is also not in accordance with SAK-EMKM.